Sphingosine-1-Phosphate Induces Dose-Dependent Chemotaxis or Fugetaxis of T-ALL Blasts through S1P1 Activation - Messias, Carolina V.; Santana-Van-Vliet, Eliane; Lemos, Julia P.; Moreira, Otacilio C.; Cotta-de-Almeida, Vinicius; Savino, Wilson; Mendes-da-Cruz, Daniella Arêas (PLOS ONE, 2016)
Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid involved in several physiological processes including cell migration and differentiation. S1P signaling is mediated through five G protein-coupled receptors (S1P1-S1P5). S1P1 is crucial to the exit of T-lymphocytes from the thymus and peripheral lymphoid organs through a gradient of S1P. We have previously observed that T-ALL and T-LBL blasts express S1P1. Herein we analyzed the role of S1P receptors in the migratory pattern of human T-cell neoplastic blasts. S1P-triggered cell migration was directly related to S1P1 expression. T-ALL blasts expressing low levels of S1P1 mRNA (HPB-ALL) did not migrate toward S1P, whereas those expressing higher levels of S1P1 (MOLT-4, JURKAT and CEM) did migrate. The S1P ligand induced T-ALL cells chemotaxis in concentrations up to 500 nM and induced fugetaxis in higher concentrations (1000–10000 nM) through interactions with S1P1. When S1P1 was specifically blocked by the W146 compound, S1P-induced migration at lower concentrations was reduced, whereas higher concentrations induced cell migration. Furthermore, we observed that S1P/S1P1 interactions induced ERK and AKT phosphorylation, and modulation of Rac1 activity. Responding T-ALL blasts also expressed S1P3 mRNA but blockage of this receptor did not modify migratory responses. Our results indicate that S1P is involved in the migration of T-ALL/LBL blasts, which is dependent on S1P1 expression. Moreover, S1P concentrations in the given microenvironment might induce dose-dependent chemotaxis or fugetaxis of T-ALL blasts.